Identification and analysis of uncertainty in disaster risk reduction and climate change adaptation in South and Southeast Asia - Van Der Keur, Peter; Mukerjee, Nandan; Bers, Caroline van; Henriksen, Hans Jørgen; Nibanupudi, Hari Krishna; Yadav, Shobha; Wijaya, Rina; Subiyono, Andreas; Hausmann, Hans-Jakob; Hare, Matt; Scheltinga, Catharien Terwisscha van; Pearn, Gregory; et al. (© 2016 Elsevier Ltd., 2016)
This article was published in International Journal of Disaster Risk Reduction [© 2016 Elsevier Ltd.] and the definite version is available at: http://www.sciencedirect.com/science/article/pii/S2212420915301321